2016
DOI: 10.1038/srep38297
|View full text |Cite
|
Sign up to set email alerts
|

Internal luminescence efficiencies in InGaP/GaAs/Ge triple-junction solar cells evaluated from photoluminescence through optical coupling between subcells

Abstract: In-situ characterization is one of the most powerful techniques to improve material quality and device performance. Especially in view of highly efficient tandem solar cells this is an important issue for improving the cost-performance ratio. Optical techniques are suitable characterization methods, since they are non-destructing and contactless. In this work, we measured the power dependence of photoluminescence (PL) from the InGaP and GaAs subcells of an industry-standard triple-junction solar cell. High lum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Characterization of optoelectronic devices with photoluminescence (PL) is fast, highly sensitive, contactless, and non-destructive. It is useful since PL directly reflects the device quality [14][15][16][17]. With regard to the information about the carrier dynamics, the PL spectra easily allow for individual characterization of different subcells, which is essential for tandem solar cell engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Characterization of optoelectronic devices with photoluminescence (PL) is fast, highly sensitive, contactless, and non-destructive. It is useful since PL directly reflects the device quality [14][15][16][17]. With regard to the information about the carrier dynamics, the PL spectra easily allow for individual characterization of different subcells, which is essential for tandem solar cell engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Considering photon recycling negligible can be a source of error in evaluating thermal losses especially in the case of stacked multi-junction solar cells [11][12][13]. However in this work we will show that radiative recombination accounts for a very small fraction of the whole loss (1-3%) showing how this assumption leads to marginal inaccuracies only.…”
Section: Theoretical Frameworkmentioning
confidence: 66%
“…Characterization of luminescence from solar cells is useful for estimation of the internal energy loss. In particular, the external luminescence efficiency ( η ext ) and the internal luminescence efficiency ( η int ) can be used for the quantitative analysis of non‐radiative recombination losses in III–V solar cells: η ext is the ratio of photon flux exiting the cell to the total carrier recombination rate, and η int is the probability of radiative emission in a single electron–hole recombination event. Based on the detailed balance theory and the reciprocity relation between electroluminescence (EL) intensity and external quantum efficiency (EQE) spectrum, it has been shown that the quantitative current–voltage (J–V) characteristics and the voltage losses in each subcell of a MJ solar cell can be evaluated by using η ext .…”
Section: Introductionmentioning
confidence: 99%